2020
DOI: 10.1001/jamaoto.2019.4029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety of Intralesional Cidofovir for Adjuvant Treatment of Recurrent Respiratory Papillomatosis

Abstract: ecurrent respiratory papillomatosis (RRP) is a disease characterized by benign papillomatous lesions of the upper airway that often cause debilitating dysphonia and may result in airway obstruction. Because of its recurrent nature, multiple surgical excisions are required to manage RRP, resulting in patient morbidity and high health care use. 1,2 Intralesional injections of the antiviral medication cidofovir have been used in an attempt to decrease the frequency of excisions and reduce the burden of disease fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The intraoperative supply of Cidofovir is a safe procedure as it is not associated with an increased risk of dysplasia or carcinoma or a statistically significant increase in complications 6 . Other side effects of Cidofovir treatment enlisted by Broekema and Dikkers 14 : cutaneous rash, headache, local inflammatory response, vocal cord scarring, compromised airway, disorders of hematologic, and chemical parameters in blood were not reported in our research group.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The intraoperative supply of Cidofovir is a safe procedure as it is not associated with an increased risk of dysplasia or carcinoma or a statistically significant increase in complications 6 . Other side effects of Cidofovir treatment enlisted by Broekema and Dikkers 14 : cutaneous rash, headache, local inflammatory response, vocal cord scarring, compromised airway, disorders of hematologic, and chemical parameters in blood were not reported in our research group.…”
Section: Discussionmentioning
confidence: 53%
“…13 The intraoperative supply of Cidofovir is a safe procedure as it is not associated with an increased risk of dysplasia or carcinoma or a statistically significant increase in complications. 6 Other side effects…”
Section: Discussionmentioning
confidence: 99%
“… 25 However, a more recent study demonstrated that IL cidofovir use in patients with RRP did not increase rates of dysplasia or carcinoma development compared with control RRP patients. 26 …”
Section: Adverse Events and Special Considerationsmentioning
confidence: 99%
“…25 However, a more recent study demonstrated that IL cidofovir use in patients with RRP did not increase rates of dysplasia or carcinoma development compared with control RRP patients. 26 Large-scale studies addressing the need for laboratory monitoring of patients undergoing treatment with IL cidofovir are lacking. Regardless of administration route, one should consider close monitoring for possible nephrotoxicity through serum creatinine levels in patients who have preexisting renal dysfunction, require a large dose of cidofovir, or are on other medications that modify rates of renal excretion.…”
Section: Administration and Dosage Of Medicationmentioning
confidence: 99%
“…Use of adjuvant intralesional cidofovir remains controversial given the paucity of controlled clinical data yet continued widespread use. Continued use of cidofovir is supported by some retrospective studies suggesting a clinical benefit and evidence that there is little chance of harm with repeat administration 32 . Until more definitive and convincing clinical evidence emerges for other forms of adjuvant treatment for RRP, use of intralesional cidofovir will likely continue in select practices.…”
Section: Summary On Antiviral Antiangiogenic and Other Adjuvant Treatments For Rrpmentioning
confidence: 99%